1994
DOI: 10.1200/jco.1994.12.10.2193
|View full text |Cite
|
Sign up to set email alerts
|

Phase I and pharmacodynamic study of the topoisomerase I-inhibitor topotecan in patients with refractory acute leukemia.

Abstract: These results indicate that substantial dose escalation of TPT above myelosuppressive doses reached in solid-tumor patients is feasible in patients with refractory leukemia, that biologically relevant TPT Css values are achievable, and that further developmental trials are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
81
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(86 citation statements)
references
References 18 publications
5
81
0
Order By: Relevance
“…irinotecan and its active metabolite SN-38, TPT, 9-aminocamptothecin (9-AC) and GI-147211 (Sinha, 1995). These drugs show a broad spectrum of anti-cancer activity in preclinical and clinical studies (Giovanella et al, 1989;Rowinsky et al, 1992;Slichenmyer et al, 1993;Potmesil, 1994;Rowinsky et al, 1994;Tanizawa et al, 1994;Sinha, 1995;Conti et al, 1996). However, tumours may develop clinical resistance against these topo I inhibitors.…”
mentioning
confidence: 99%
“…irinotecan and its active metabolite SN-38, TPT, 9-aminocamptothecin (9-AC) and GI-147211 (Sinha, 1995). These drugs show a broad spectrum of anti-cancer activity in preclinical and clinical studies (Giovanella et al, 1989;Rowinsky et al, 1992;Slichenmyer et al, 1993;Potmesil, 1994;Rowinsky et al, 1994;Tanizawa et al, 1994;Sinha, 1995;Conti et al, 1996). However, tumours may develop clinical resistance against these topo I inhibitors.…”
mentioning
confidence: 99%
“…In renal cell cancer (Ilson et al, 1993;Law et al, 1994) and colorectal cancer (Sugarman et al, 1994) the drug appears inactive. Little phase II experience has been reported for haematological tumours, although responses in phase I trials have been observed in patients with relapsed or refractory acute leukaemia (Kantarjian et al, 1993;Rowinsky et al, 1994).…”
Section: Resultsmentioning
confidence: 99%
“…Topo has shown clinical activity in many tumour types, for example ovarian carcinoma (Gore et al, 1996), NSCLC (PerezSolar et al, 1996) and leukaemia (Kantarjian et al, 1993;Rowinsky et al, 1994).…”
mentioning
confidence: 99%
“…Further studies on BTBD1 and BTBD2 are thus required to fill in the gaps concerning molecular events that regulate Topo1 activity, its involvement in vital biological functions such as mitosis and transcription, 3,[36][37][38] and in severe pathologies such as cancer and leukaemia. [15][16][17][18][19][20] Here we attempted to elucidate BTBD1 function in skeletal muscle, where this protein is mostly expressed.…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore not surprising that repression or overexpression of the Topo1 gene can lead to cell death, [12][13][14] indicating that preservation of a normal level of Topo1 is crucial for cell survival. Moreover, Topo1 is more abundant in acute lymphocytic leukaemia and several human tumours than in normal tissue, [15][16][17][18][19][20] possibly because of a defect in its degradation, 21 and Topo1 inhibitors are used as antitumour agents. Although many proteins have been described as interacting with Topo1 to regulate its activity.…”
Section: Introductionmentioning
confidence: 99%